If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5x + -7) = 6 Reorder the terms: ln(-7 + 5x) = 6 (-7 * ln + 5x * ln) = 6 (-7ln + 5lnx) = 6 Solving -7ln + 5lnx = 6 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -6 + -7ln + 5lnx = 6 + -6 Combine like terms: 6 + -6 = 0 -6 + -7ln + 5lnx = 0 The solution to this equation could not be determined.
| (x-2c)(2x+c)+cx= | | 2y/5=12 | | 6c+2A=38 | | A=1/2(4)(4) | | 72/18 | | A=1/2(4/5)(4/5) | | A=1/2(16)(12) | | (6x-7)=(2x-7) | | 3b+b=b+12 | | A=1/2(14)(14) | | x+2/3=0 | | 9-4(2)(1)= | | 800+0.25x=x | | n+11=17 | | A=1/2(32)(32) | | 2x^2-9x+4=22 | | (2x-1)(x-4)=22 | | 4x+47=83 | | 4x+47=63 | | 12x+7y=155 | | 4x-2=12-122 | | y+11y=-10 | | t^2-10t-80=0 | | (2x^2-3)+(3x^2+4)=0 | | 3x-10=-34 | | -16x^2+34x+50=0 | | 0.80=(925.4-33.05x)/(925.4-28x) | | 16x^2+34x+50=0 | | 7x-7=-21 | | (2x+5)-(4x-6)=0 | | 2x+1/2-6x-1/4=-5/12 | | 46+4= |